REFORMASI PEMBANGUNAN PERTANIAN INDONESIA MELALUI AGROBISNIS - Fakultas Pertanian UNISRI, Priyono (MAJALAH ILMIAH GEMA, 2002)
Based on the experiments, the agribusiness application is profitable enough, for examples : 1) about 40 million of agriculture sector employment in 2000 (70% of national employment), or almost 80% of Indonesian people live economically from agribusiness sector. The food problem is a serious challenge that needs to be solved soon and attained its stability. 2) As long as PJP I/fist PJP, Indonesian can be self supporting in agriculture in 1984, and 50% of national employment can be absorbed by the agriculture sector. Agriculuter can give contribution to increase the incomer per capita from US $ 70 in 1969 become US $ 700 in the end firdt PJP. 3) Today during the crisis period agriculture product (society agriculuter industry) has been booming, while the broad based industry and hitech industry has been collapse. Based on that experience the new way of the agribusiness application (form the beginning to the end of agrbibusiness) is expected to increase the living standard of citizen and give contribution in managing economy is a must. The result of agribusiness development is including in increasing the income, improving the job appotunity, providing enough food coping poverty and preserving environment,act Key word:  agriculture, agribusiness, reform